2010
DOI: 10.1523/jneurosci.3352-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Protein Kinase C Regulates Primary Dendrite Specification of Cerebellar Purkinje Cells by Localizing Golgi Apparatus

Abstract: Neurons have highly polarized structures that determine what parts of the soma elaborate the axon and dendrites. However, little is known about the mechanisms that establish neuronal polarity in vivo. Cerebellar Purkinje cells extend a single primary dendrite from the soma that ramifies into a highly branched dendritic arbor. We used the zebrafish cerebellum to investigate the mechanisms by which Purkinje cells acquire these characteristics. To examine dendritic morphogenesis in individual Purkinje cells, we m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
75
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 55 publications
(75 reference statements)
6
75
0
Order By: Relevance
“…This antiserum also recognizes phosphorylated PKCι, the other atypical PKC that shares a nearly identical C-terminus with PKCζ (Hernandez et al, 2003). PKCι, however, localizes to the cell body and nucleus (White et al, 2002) and is involved in organization of the Golgi apparatus (Tanabe et al, 2010) and microtubules (Tisdale, 2002), both of which are absent in the dendritic spine. Although PKMζ immunolabeling is indistinguishable from PKCζ immunolabeling due to their identical amino acid sequence, PKMζ is expressed in the forebrain as the major form of ζ in the near absence of PKCζ in rodents (Hernandez et al, 2003; Oster et al, 2004) and in humans (Crary et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…This antiserum also recognizes phosphorylated PKCι, the other atypical PKC that shares a nearly identical C-terminus with PKCζ (Hernandez et al, 2003). PKCι, however, localizes to the cell body and nucleus (White et al, 2002) and is involved in organization of the Golgi apparatus (Tanabe et al, 2010) and microtubules (Tisdale, 2002), both of which are absent in the dendritic spine. Although PKMζ immunolabeling is indistinguishable from PKCζ immunolabeling due to their identical amino acid sequence, PKMζ is expressed in the forebrain as the major form of ζ in the near absence of PKCζ in rodents (Hernandez et al, 2003; Oster et al, 2004) and in humans (Crary et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Polarity complexes include evolutionarily conserved apical complex proteins, such as the Crb complex (comprising Crbs, Pals1, Patj), the Par complex (Par3, Par6, aPKC) and basal complex proteins, such as the Scribble complex (Scribbles, Lgl, Dlg) (Assémat et al, 2008;Pieczynski and Margolis, 2011;Tepass, 2012). Previous studies have demonstrated that apical complex proteins are necessary for self-renewal of neural progenitor cells (Bultje et al, 2009;Costa et al, 2008;Kim et al, 2010), neuronal migration (Famulski et al, 2010;Solecki et al, 2006), axon determination (Chen et al, 2013;Shi et al, 2003), dendrite development (Tanabe et al, 2010), tissue polarity and neuron survival (Kim et al, 2010). However, there is little information about the function of apical complex proteins in the regulation of proliferation and differentiation of CGNPs, which lack typical apical-basal polarity.…”
Section: Introductionmentioning
confidence: 99%
“…1 entiation of a neurite into an axon (22). Recent studies have indicated that the aPKC-Par3-Par6 complex participates in neurite outgrowth before and after axon differentiation, as well as in dendrite formation (23)(24)(25). Of note, Wnt4 attracts the outgrowth of commissural axons by a mechanism that relies on aPKC (24).…”
mentioning
confidence: 99%